STRATEGY TO PLANTING AND GROWING A NEW CHURCH IN THE ERA OF THE COVID-19 PANDEMIC - Ferry Simanjuntak; Christie Putri Sion; Diana Tri Agustine (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Today the church is starting to develop in terms of worship and in terms of teaching because a wider world can be reached through technological advances. Whatever form, model, and system developed in the management of the Church, it must adhere to the basic and essential ideas of the Church according to the Bible. The research used in this paper is a literature study method, which is a study used to collect information and data with the help of various materials such as books and journal articles. In the current Covid-19 pandemic, churches are very dependent on digital media for plant survival and church growth.This research provides a new contribution and perspective for the church about ministry in the pandemic era. This research provides new information about ministry development, evangelism and discipleship in the church